2005
DOI: 10.1136/bjo.2004.057778
|View full text |Cite
|
Sign up to set email alerts
|

Clinical evaluation of frequency doubling technology perimetry using the Humphrey Matrix 24-2 threshold strategy

Abstract: Aims: To evaluate performance of frequency doubling technology (FDT) perimetry using the Humphrey Matrix 24-2 thresholding program in a hospital eye service (HES) glaucoma clinic. Methods: A random sample of individuals referred consecutively to the HES for suspected glaucoma were examined with 24-2 threshold FDT in addition to routine clinical tests. The discriminatory power of FDT and standard automated perimetry (SAP) were assessed using glaucomatous optic nerve head appearance as the reference gold standar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
63
1
1

Year Published

2007
2007
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(70 citation statements)
references
References 12 publications
4
63
1
1
Order By: Relevance
“…Spry and colleagues, 176 in a cohort study set in the UK, reported the test accuracy of the FDT C-20 matrix (Humphrey matrix 24-2). An abnormal test result was defined as a GHT outside the normal limit and/or p < 0.05 with the pattern standard deviation global index in one or both eyes.…”
Section: Fdt (C-20 Full Threshold and C-20 Matrix)mentioning
confidence: 99%
See 2 more Smart Citations
“…Spry and colleagues, 176 in a cohort study set in the UK, reported the test accuracy of the FDT C-20 matrix (Humphrey matrix 24-2). An abnormal test result was defined as a GHT outside the normal limit and/or p < 0.05 with the pattern standard deviation global index in one or both eyes.…”
Section: Fdt (C-20 Full Threshold and C-20 Matrix)mentioning
confidence: 99%
“…164 For the common cut-off, sensitivity ranged from 25% (sufficient points to drop the indicator into the suspicious zone or below) 164 to 90% (at least four abnormal points in any single quadrant), 162 while specificity ranged from 67% (absolute or relative defects ജ17) 168 to 96% (sufficient points to drop the indicator into the suspicious zone or below). 164 The pooled sensitivity, specificity and DOR from the meta-analysis models for the common cut-off 186 Ivers, 2001 157 Katz, 1993 159 Marraffa, 1989 174 Mundorf, 1989 162 Vernon, 1990 164 Vitale, 2000 166 Wang, 1998 157 Katz, 1993 159 Mundorf, 1989 162 Vernon, 1990 164 Wang 1998 168 Harper, 1994 182 Ieong 176 and two case-control studies.…”
Section: Figure 31(a) and (B)mentioning
confidence: 99%
See 1 more Smart Citation
“…Most reports that compare the results of Humphrey Matrix with those of the Humphrey Field Analyser indicate that the two VF techniques produce similar results. 27 Additionally, HMP has been reported to have reasonably uniform variability properties for all levels of glaucomatous VF loss, 24 and some studies have suggested that FDT testing may be useful for determining glaucomatous visual progression. 7,28 In SAP, a learning effect can influence the results of the VF test in both healthy and glaucomatous patients.…”
Section: Discussionmentioning
confidence: 99%
“…Similar to SAP, FDT Matrix also provides raw sensitivity values, total and pattern deviation probability plots, and the summary indices of MD and PSD. Matrix FDT has been reported by some to be better than SAP for discriminating glaucomatous and healthy eyes (Racette et al, 2008); however, others found no difference between Matrix FDT and SAP (Spry et al, 2005). SWAP has also been modified over the years and now utilizes the SITA strategy to shorten the test duration.…”
Section: Figurementioning
confidence: 99%